Tele-Neurorehabilitation During the COVID-19 Pandemic: Implications for Practice in Low- and Middle-Income Countries - Srivastava, Abhishek; Swaminathan, Aishwarya; Chockalingam, Manigandan; Srinivasan, Murali K.; Surya, Nirmal; Ray, Partha; Hegde, Prasanna S.; Akkunje, Preetie Shetty; Kamble, Sanjivani; Chitnis, Sonal; Kamalakannan, Sureshkumar; Ganvir, Suvarna; et al. (Frontiers in Neurology, 2021)
The importance of neurorehabilitation services for people with disabilities is getting well-recognized in low- and middle-income countries (LMICs) recently. However, accessibility to the same has remained the most significant challenge, in these contexts. This is especially because of the non-availability of trained specialists and the availability of neurorehabilitation centers only in urban cities owned predominantly by private healthcare organizations. In the current COVID-19 pandemic, the members of the Task Force for research at the Indian Federation of Neurorehabilitation (IFNR) reviewed the context for tele-neurorehabilitation (TNR) and have provided the contemporary implications for practicing TNR during COVID-19 for people with neurological disabilities (PWNDs) in LMICs. Neurorehabilitation is a science that is driven by rigorous research-based evidence. The current pandemic implies the need for systematically developed TNR interventions that is evaluated for its feasibility and acceptability and that is informed by available evidence from LMICs. Given the lack of organized systems in place for the provision of neurorehabilitation services in general, there needs to be sufficient budgetary allocations and a sector-wide approach to developing policies and systems for the provision of TNR services for PWNDs. The pandemic situation provides an opportunity to optimize the technological innovations in health and scale up these innovations to meet the growing burden of neurological disability in LMICs. Thus, this immense opportunity must be tapped to build capacity for safe and effective TNR services provision for PWNDs in these settings.